Improving Grade VII Students’ Achievement in Procedure Text Through Still Pictures - Berta Ito Lubis and Tina Mariany Arifin (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2013)
This study was conducted as an attempt to improve students’ writing achievement in aprocedure text by using Still Pictures. The method of the study was Classroom ActionResearch with two cycles and six meetings. The subject of the study was the students ofGrade VII students’ MTs. S. Syahbuddin Mustafa Nauli. The research was conducted intwo cycles and each cycle consists of three meetings. The instruments for collectingdata were taken from writing tests as quantitative data. The result shows theimprovement of the students’ score from orientation test to Cycles I and II tests. Themean of the students’ score for orientation test as Test I was 50.41, Cycle I test was66.25, and Cycle II test was 85.41. The total percentage of the improvement fromOrientation test to Cycles I and II tests was 99.2 %. It can be concluded that the use ofStill Pictures improves students’ achievement in writing a procedure text. Thequalitative data taken from Observation Sheet and Diary Notes show that the students’were enthusiastic and attracted in writing a procedure text because the Still Picturesencourage their creativities and ideas to write better. For English teachers, it issuggested to use Still Pictures as one alternative media of teaching writing a proceduretext.